Jula-Jula as a Model of Shariah-Compliant Microfinance: Community Practices in Rural Indonesia - Herispon, Herispon; Anuar, Saiful; Jenita, Jenita (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
This study explores the indigenous Rotating Savings and Credit Association (ROSCA) known as Jula-Jula, as practiced in Tarai Bangun, a rural area in Riau Province, Indonesia. While exhibiting characteristics of global ROSCA models, Jula-Jula is deeply interwoven with the local cultural, social, and religious fabric. Employing a qualitative phenomenological approach involving observations, interviews with ten members and five collectors, and documentation, this research (i) identifies and describes the distinct operational models of Jula-Jula prevalent within the community and (ii) analyzes their economic, financial, and social ramifications through the lens of Islamic finance principles. The findings reveal three primary operational models based on contribution frequency—monthly, weekly, and daily—alongside two structural variations: Jula-Jula No Fee, which emphasizes mutual support without financial charges, and Jula-Jula With Fee, characterized by modest, transparent service fees mutually agreed upon to compensate collectors for logistical efforts. This study underscores the significant role of Jula-Jula in fostering financial inclusion, providing interest-free microfinance opportunities, and enhancing community resilience. These practices are found to be consistent with core Islamic economic tenets, including the prohibition of riba (interest), the promotion of maslahah (benefit), adl (justice), and ta’awun (cooperation). Ultimately, this research contributes to the ongoing discourse on ethical and community-driven financial systems, demonstrating the potential of localized Shariah-compliant models to complement or serve as alternatives to formal financial institutions in underbanked regions.========================================================================================================ABSTRAK - Jula-Jula sebagai Model Keuangan Mikro Syariah berbasis Komunitas di Indonesia. Penelitian ini mengkaji praktik Jula-Jula, sebuah model simpan pinjam bergilir (ROSCA) yang dipratikkan di Desa Tarai Bangun, Kampar, Riau, Indonesia. Sistem keuangan informal ini dikenal secara lokal sebagai Jula-Jula, memiliki kesamaan dengan praktik ROSCA global, namun terintegrasi secara mendalam dengan nilai-nilai budaya, sosial, dan keagamaan masyarakat setempat. Penelitian ini bertujuan untuk (i) mengidentifikasi dan mendeskripsikan model Jula-Jula yang dipraktikkan dalam masyarakat, dan (ii) menganalisis implikasi ekonomi, finansial, dan sosialnya dalam kerangka keuangan Islam. Data untuk penelitian ini dikumpulkan melalui observasi, wawancara, dan dokumentasi terhadap sepuluh anggota dan lima pengelola Jula-Jula dan dianalisis dengan pendekatan fenomenologi kualitatif. Hasil penelitian menunjukkan tiga model operasional—kontribusi bulanan, mingguan, dan harian—dengan dua tipe struktur utama: Jula-Jula Tanpa Biaya yang menekankan dukungan bersama tanpa imbalan keuangan, dan Jula-Jula dengan Biaya, yang menerapkan biaya layanan secara sukarela dan transparan untuk mendukung operasional kolektor. Studi ini menyoroti peran Jula-Jula dalam memperluas inklusi keuangan, menyediakan pembiayaan mikro tanpa riba, serta memperkuat ketahanan masyarakat. Praktik ini selaras dengan prinsip-prinsip ekonomi Islam, seperti larangan riba, penerapan maslahah, keadilan, dan ta’awun (kerja sama). Penelitian ini berkontribusi pada wacana keuangan etis berbasis komunitas, serta menunjukkan bahwa model keuangan lokal yang sesuai syariah dapat melengkapi atau menggantikan institusi formal di wilayah yang belum terjangkau layanan keuangan formal.